Blackbox modelling of a 6 rotor helicopter - Balya, Darohini; Muhammad Izzat Faez, Yusuf; M. F., Abas; N., Md. Saad; Pebrianti, Dwi; M. Z., Ibrahim (UTeM, 2018)
Aerial robotics have received a considerable interest in both private builders and research laboratories for several years. In this respect, modeling is needed in the first step of developing aerial robotics or multi-rotor UAV and there are various methods that can be used for modeling. In this paper, the authors discussed and compared two types of blackbox modeling method that is the Continuous State Space using PEM method and the commonly used Second Order Underdamped System with Delay process model. Based on a comparison analysis of the two methods drawn from experimental data, it was found that the Second Order Underdamped System with Delay Modeling gives better similarity for a hexarotor pitch angle model. In contrast, the Continuous State Space model using PEM method in Polynomial gives better similarity to the hexarotor roll angle model. Finally, both tested methods deliver similar similarity for hexarotor yaw angle model.